IMPLEMENTING EFFECTIVE CORPORATE INTERNAL CONTROL AND DEVELOPING GOOD CORPORATE GOVERNANCE - Suka Negara, I Wayan (Buletin Studi Ekonomi, 2016)
Implementing Effective Corporate Internal Control And Developing Good Corporate Governance. Internal control and good corporate governance are acknowledged as an important component in corporation. Both concepts assist corporation to achieve its objectives. However, some people think that both concepts are different and do not have relationship each other. For this reason, this paper tries to explain what both concepts are and their relationship between them as a useful guideline for corporation to achieve its goals. Based on the analysis conducted, it is obtained the result that both internal control concept and GCG’s concept are the mutual complementary concept. The success of implementing internal control concept depends on a success of implementing GCG’s concept and vice versa.   Keywords: internal control, good corporate governance
Keywords: internal control, good corporate governance